Non-tariff barriers in Malaysia's agricultural and manufacturing sectors : their determinants and impacts on imports - Azlina binti Hanif (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2010)
The successive General Agreement on Tariffs and Trade (GATT) rounds of multilateral trade negotiations have generally led to significant tariff reductions in many countries. Given the relatively low tariff environment, focus is now directed onto the rising importance of non-tariff barriers (NTBs) as a protectionist and regulatory trade policy tool. However, studies pertaining to NTBs are relatively scarce. Thus, the present study seeks to identify the incidence and determinants of NTBs in Malaysia's agricultural and manufacturing sectors. The impact of NTBs on import in each sector is also examined. The level of NTBs measured in these sectors reveal that agricultural NTBs has increased over the years while that of manufacturing is relatively lower and has remained somewhat stable. Findings from the ARDL cointegration analysis suggest that the level of NTBs in the agriculture sector appears to be influenced by the sector's import penetration ratio, average tariff rate, competitiveness and employment growth. Meanwhile, the level of NTBs in the manufacturing sector is influenced only by sectoral competitiveness. Despite the imposition of NTBs on imports, aggregate imports in both the agricultural and manufacturing sectors over the 1978 and 2007 period are not affected by their presence. Instead, agricultural import is influenced by other factors such as real income in the long run and relative price in the short run. The VAR analysis conducted also reveals that real income is the only significant factor which influences aggregate manufacturing import albeit briefly. At a disaggregated level, results from OLS in first differences show that an increase in the growth of NTBs does in fact reduce the import growths of most of the HS-9 digit products examined. Based on the outcome of the study, trade policies with regard to the imposition or removal of NTBs should be formulated on a product-by-product or industry-by-industry basis.